THE RESEARCH OF MESOZOIC THEROPODS IN GONDWANA: A BRIEF HISTORICAL OVERVIEW (Ameghiniana, 2017)
The study of Gondwanan non-avian theropods has been outstandingly prolific in the last three decades and has shown that the taxonomic and morphological diversity of the group is comparable to that of Laurasia. As a consequence of this diversity, the Gondwanan non-avian theropod record has been crucial to understand the evolution and global biogeography of dinosaurs during the Mesozoic. However, the history of the research of the southern theropods has been heterogeneous in the last century and only in 2004 we reached the 50% of all the valid Gondwanan theropod species currently known. Here we propose that the history of the Gondwanan theropod research can be divided in three different stages.